Annual Appearance of Hydrogen Chloride on Mars and a Striking Similarity With the Water Vapor Vertical Distribution Observed by TGO/NOMAD. Issue 11 (3rd June 2021) - Aoki, S.; Daerden, F.; Viscardy, S.; Thomas, I. R.; Erwin, J. T.; Robert, S.; Trompet, L.; Neary, L.; Villanueva, G. L.; Liuzzi, G.; Crismani, M. M. J.; Clancy, R. T.; et al.
Abstract: Hydrogen chloride (HCl) was recently discovered in the atmosphere of Mars by two spectrometers onboard the ExoMars Trace Gas Orbiter. The reported detection made in Martian Year 34 was transient, present several months after the global dust storm during the southern summer season. Here, we present the full data set of vertically resolved HCl detections obtained by the NOMAD instrument, which covers also Martian year 35. We show that the particular increase of HCl abundances in the southern summer season is annually repeated, and that the formation of HCl is independent from a global dust storm event. We also find that the vertical distribution of HCl is strikingly similar to that of water vapor, which suggests that the uptake by water ice clouds plays an important role. The observed rapid decrease of HCl abundances at the end of the southern summer would require a strong sink independent of photochemical loss. Plain Language Summary: A new species, hydrogen chloride (HCl), was recently discovered in the atmosphere Mars. Whereas, this gas plays a key role in the atmospheric chemistry on Earth and Venus, the chlorine cycle on Mars is not understood. HCl was found just after the global dust storm, so a connection between the storm and appearance of HCl was suggested. This study shows that HCl is detected even in a year without a global dust storm, which demonstrates that the formation of HCl is primary independent from global dust storms. This study also finds that the vertical distributions of HCl and water vapor are strikingly similar in shape. As the vertical profile of water vapor is controlled by the formation of water ice clouds, it suggests that HCl is taken up by water ice clouds. Finally, we observe that HCl is rapidly disappearing at the end of the southern summer on Mars. We demonstrate that this fast destruction cannot be explained by the standard photochemistry, which suggests that another (unknown) process plays a key role. Key Points: Increase of hydrogen chloride (HCl) during the southern summer is annually repeated. It shows that HCl formation is independent from a global dust storm Vertical distributions of HCl are strikingly similar to water vapor. It suggests that uptake by water ice clouds plays an important role A rapid decrease of HCl at the end of the southern summer suggests the presence of a strong sink in addition to the photochemical loss